Fintech Lending Adoption among Muslim Millennials : Toward Inclusive and Ethical Sharia Banking in Southeast Asia - Safira, Nabila; Inayatillah; Meutia, Rachmi; Kamri, Nor ‘Azzah; Yusof, Ku Abdulmuhaimin (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2025)
Purpose – This study aims to analyze the economic, social, and cultural factors influencing fintech lending adoption among Muslim millennials in these three nations while critically assessing the regulatory and ethical challenges of integrating Islamic financial principles into digital lending ecosystems Method – This research employs a comparative qualitative approach, integrating survey data, semi-structured interviews, and policy analysis to examine the regulatory landscapes and consumer behavior in Indonesia, Malaysia, and Thailand. Findings – The findings indicate that Malaysia leads in Islamic fintech adoption, supported by a well-regulated and structured Sharia-compliant financial system. Indonesia demonstrates high fintech penetration but suffers from low consumer awareness regarding Islamic digital finance alternatives. Thailand, in contrast, lacks a formal Islamic fintech framework, which has led to low adoption rates despite the presence of Muslim-majority provinces. Practical implications – The study offers important theoretical implications by bridging Islamic finance principles with digital financial innovation and contributing to the literature on fintech adoption in Muslim-majority and minority regions. The practical implications suggest that ASEAN policymakers should harmonize Islamic fintech regulations to enable cross-border collaborations, expand Sharia-compliant fintech to underserved Muslim populations, and develop financial literacy initiatives to enhance consumer trust in digital Islamic finance. Originality/value – This study provides Southeast Asia comparative ASEAN Muslim-majority vs minority fintech on Islamic fintech adoption, an underexplored area in existing research